2014
DOI: 10.1111/1755-6724.12219
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Developmental Characteristics and Response to Climate Change since the Last Glacial in the Upper Reaches of the Yellow River, NE Tibetan Plateau

Abstract: : The upper reaches of the Yellow River in northeastern Tibetan Plateau are geohazards areas. The evolution of the Yellow River, chronology of some landslides, and spatiotemporal distribution characteristics of super large scale and giant landslides within the region are summarized using paleoclimate evidence, and the relationship between the intensive landslide period and climatic changes since the Last Glacial period is analyzed. It is concluded that (1) Super large scale and giant landslides are distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…1(c)] shows that the lithology and thickness of the strata in the area of Xunhua-Jianzha-Qunke vary greatly; the upper strata are mainly Neogene sandstone, mudstone, and sand conglomerate, with exposed Quaternary fine sand, silt, and loess interlayers. The loose lithology of the strata provides the material basis for the swarm formation of landslides [63].…”
Section: A Clustering Mechanism Of Detected Active Landslidesmentioning
confidence: 99%
“…1(c)] shows that the lithology and thickness of the strata in the area of Xunhua-Jianzha-Qunke vary greatly; the upper strata are mainly Neogene sandstone, mudstone, and sand conglomerate, with exposed Quaternary fine sand, silt, and loess interlayers. The loose lithology of the strata provides the material basis for the swarm formation of landslides [63].…”
Section: A Clustering Mechanism Of Detected Active Landslidesmentioning
confidence: 99%
“…From the hydrological point of view, the Huangshui River, 374 km long, originates in the north part of Tibet at an elevation of 4000 m, and flows eastwards into the Yellow River in Gansu Province, becoming a first-order tributary. The study area is characterized also by very steep slopes and narrow valleys, with height difference up to 900 m [8]. The regional climate is characteristically plateau arid and continental semi-arid with 34 • C during summer and −20 • C during winter on average.…”
Section: Study Areamentioning
confidence: 99%
“…Many researchers have reported that Qing-Tibet Plateau (QTP) has experienced warming and wetting trends, and the precipitation amount and the number of precipitation days have increased drastically during past decades [6,7]. For this reason, the upper reaches of the Yellow River-Huangshui Basin, located in the northeastern edge of QTP, became a disaster-prone region where numerous loess landslides occurred in recent years (Figure 1) [8]. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Local influence studies have been investigated using total/cumulative precipitation, precipitation intensity, air temperature, weather system (Collison et al, 2000;Malet et al, 2005;Tommasi et al, 2006;Dixon and Brook, 2007;Rianna et al, 2014;Zollo et al, 2014), regionally for areas ranging from a few 100 m 2 to a few 1000 km 2 (Rebetez et al, 1997;Malet et al, 2007;Gariano et al, 2015;Ciabatta et al, 2016), nationally or supra-regionally (Sidle & Dhakal, 2002;Schmidt & Glade, 2003;Winter et al, 2010;Stoffel et al, 2014;Paranunzio et al, 2016). The short-term impacts of climate change span from a few years to a century or two, while the long-term impacts are measured from several centuries to several millennia (Trauth et al, 2000;Schmidt & Dikau, 2004;Borgatti & Soldati, 2010;Yin et al, 2014). Direct impacts of climate are those that directly affect the occurrence of landslides, such as changes in the precipitation regime that affect the amount of precipitation that can cause landslides (Guzzetti et al, 2007;Jakob & Lambert, 2009;Stoffel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%